2022
DOI: 10.3390/atmos13060977
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration of an Abandoned Grassland in the Italian Alps: Influence of Local Topography, Intra- and Inter-Annual Variability and Environmental Drivers

Abstract: Evapotranspiration is a key variable of the hydrological cycle but poorly studied in Alpine ecosystems. The current study aimed to characterise the impact of topography and temporal variability on actual evapotranspiration (ETa) and its environmental drivers at an Alpine abandoned grassland encroached by shrubs on a steep slope. Eddy covariance, meteorological, hydrological and soil data were analysed over four growing seasons, of which two had wet and two dry conditions. The topography caused a systematic mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Intermediate slopes can accommodate more trees per unit ground area than level areas, while past a certain threshold, slopes become too steep to support forest ecosystems [31,84], thus potentially influencing ET via changes in vegetation cover and tree density. In complex mountainous terrain, slope may additionally affect wind flow regimes and thus energy and water exchange [85]. It also affects soil water availability, which can constrain or enhance local ET; as such, previous studies reported enhanced (evapo)transpiration on slopes compared to waterlogged valley bottoms [77,83].…”
Section: Variable Importancementioning
confidence: 99%
“…Intermediate slopes can accommodate more trees per unit ground area than level areas, while past a certain threshold, slopes become too steep to support forest ecosystems [31,84], thus potentially influencing ET via changes in vegetation cover and tree density. In complex mountainous terrain, slope may additionally affect wind flow regimes and thus energy and water exchange [85]. It also affects soil water availability, which can constrain or enhance local ET; as such, previous studies reported enhanced (evapo)transpiration on slopes compared to waterlogged valley bottoms [77,83].…”
Section: Variable Importancementioning
confidence: 99%
“…Relevant scholars have found that solar radiation is an important factor impacting the change in evapotranspiration. Related studies have emphasized that the net radiation, photosynthetically active radiation and vapor pressure deficit are important drivers of evapotranspiration (Wieser et al, 2008;Gisolo et al 2022;Shi et al 2022).…”
Section: Correlation Between Evapotranspiration and Environmental Fac...mentioning
confidence: 99%